2016
DOI: 10.1186/s12863-016-0377-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide imputation study identifies novel HLA locus for pulmonary fibrosis and potential role for auto-immunity in fibrotic idiopathic interstitial pneumonia

Abstract: BackgroundFibrotic idiopathic interstitial pneumonias (fIIP) are a group of fatal lung diseases with largely unknown etiology and without definitive treatment other than lung transplant to prolong life. There is strong evidence for the importance of both rare and common genetic risk alleles in familial and sporadic disease. We have previously used genome-wide single nucleotide polymorphism data to identify 10 risk loci for fIIP. Here we extend that work to imputed genome-wide genotypes and conduct new RNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 52 publications
5
66
1
1
Order By: Relevance
“…Nine of these 13 loci have been associated with lung function in general population samples 27 ; however, 4 ( EEFSEC , DSP , MTCL1 , and SFTPD ) are novel. We noted 2 loci shared with pulmonary fibrosis 8,9 ( FAM13A and DSP ) but with opposite risk alleles for COPD. None of our loci overlapped with genome-wide associations for asthma; however, one locus has been implicated in the joint susceptibility to asthma and obesity 10 .…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Nine of these 13 loci have been associated with lung function in general population samples 27 ; however, 4 ( EEFSEC , DSP , MTCL1 , and SFTPD ) are novel. We noted 2 loci shared with pulmonary fibrosis 8,9 ( FAM13A and DSP ) but with opposite risk alleles for COPD. None of our loci overlapped with genome-wide associations for asthma; however, one locus has been implicated in the joint susceptibility to asthma and obesity 10 .…”
mentioning
confidence: 75%
“…To further examine overlapping loci for COPD and pulmonary fibrosis, we combined summary statistics from our study and the pulmonary fibrosis GWAS by Fingerlin et al 8,9 using gwas-pw 37 .…”
Section: Methodsmentioning
confidence: 99%
“…This study confirmed known associations with TERC , TERT and MUC5B and identified seven novel risk loci within genes involved in host defence, cell-cell adhesion and DNA repair. Recently, the same authors extended their previous work to imputed genome-wide genotypes in 1616 non-Hispanic White cases and 4683 controls followed by validation and replication in 878 cases and 2017 controls, and identified a genome-wide significant association between the human leucocyte antigen (HLA) region and fIIP 68. Notably, two HLA alleles associated with fIIP (eg, DRB1*1501 and DQB1*0602) induced differential expression of HLA genes in lung tissue, suggesting that specific immune response against unknown pulmonary targets may contribute to disease pathogenesis at least in a subset of patients.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, by imputing the data of genome-wide genotypes and conducting RNA sequencing studies, they identified new fIIP risk loci in lung tissue. Fibrotic lung tissue showed a deregulation in the human leukocyte antigen region of chromosome 6 (rs7887), involving and reaffirming the role of an immune deregulation in fibrotic ILDs [46].…”
Section: Peripheral Blood Phenotypingmentioning
confidence: 74%